A New Rapid and Sensitive Spectrophotometric Method for Determination of a Biopolymer Chitosan. (26th July 2012) - Badawy, Mohamed E. I.
Abstract : A novel approach of spectrophotometric quantification of chitosan based on one-step depolymerization with sodium nitrite followed by reaction of the end product with thiobarbituric acid has been proposed, optimized, and validated. In this process, chitosan is converted into 2, 5-anhydro-D-mannose that reacts with thiobarbituric acid to form pink color. The color that resulted from the reaction was stabilized and measured at 555 nm. The method optimization was essential as many procedural parameters influenced the accuracy of the determination including hydrolysis conditions, thiobarbituric acid concentration, reaction time, pH, reaction temperature, and color stability period. Under given optimized conditions that appeared to be critical, chitosan was quantitatively analyzed and the calibration graph was linear over the range of 10–50 μ g/mL (r 2 = 0.999 ). This approach was applied for determination of chitosan in pharmaceutical formulation (chitocal) and had a recovery rate of higher than 96%. The developed method is easy to use and highly accurate.